EXPRESSION OF GENES ENCODING IMMUNOPROTEASOME SUBUNITS INDUCIBLE BY MACROPHAGES INFECTED WITH M. bovis BGC AND M. Tuberculosis H37RV - S. N. Andreevskaya; T. G. Smirnova; A. V. Timofeev; E. E. Larionova; L. N. Chernousova (Туберкулез и болезни лёгких, 2014)
To study the effect of M. bovis BCG vaccine strain and virulent laboratory M. tuberculosis H37Rv strain on the expression of macrophageinducible immunoproteasome subunits, a real-time reverse-transcription polymerase chain reaction technique using cDNA obtained with mRNA was employed to investigate gene expression. The results of infection were taken into account on days 1, 2, and 3 of inoculation. There was a difference in the time course of changes in lmp7 expression, which consisted in reducing the number of transcripts on day 3 after infection with the virulent M. tuberculosis strain versus the vaccine one. It was assumed that the inhibited transcription of this subunit, when inoculated with the virulent M. tuberculosis strain, might lead to the blocked assembly of the whole immunoproteasome and to its reduced functional activity. The investigation showed the stimulating effect of the M. bovis BCG vaccine strain against the macrophage that contributed to the presentation of major histocompatibility complex class I antigens (processed by the immunoproteasome) and the inhibitory effect of the virulent M. tuberculosis H37Rv strain.